2020
DOI: 10.1002/adom.202000519
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum‐Processed Small Molecule Organic Photodetectors with Low Dark Current Density and Strong Response to Near‐Infrared Wavelength

Abstract: A near‐infrared photodetector with optimized performance is reported using varied thickness (20, 40, 60, and 80 nm) of the active layer comprising chloroaluminium phthalocyanine (ClAlPc) and fullerene (C70) at the ratio of 1:3, and TAPC:10% MoO3 and BPhen as electron and hole blocking layers, respectively. The experimental results reveal that the photodetector with 80 nm thick active layer provides the best performance at the wavelength of 730 nm achieving a very low dark current density of 1.15 × 10−9 A cm−2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
53
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 56 publications
0
53
0
1
Order By: Relevance
“…[7,9] Nonetheless, recent efforts have led to significant boosts in the performance of NIR OPDs using either polymers [10][11][12][13] or small molecule materials. [14][15][16][17][18][19] For instance, Xiong et al investigated solutionprocessed polymer NIR OPDs with PMDPP3T:PC 61 BM bulk heterojunction (BHJ), exhibiting a low dark current density (J d ) of 3.0 nA cm −2 at −0.2 V and a high external quantum efficiency (EQE) of 48% at 850 nm (a responsivity of 0.37 A W −1 ) for broad sensing applications. [11] A further improvement on the device performance has been recently made by introducing a very thick active layer (≈300 nm) with a non-fullerene acceptor (PTB7-Th:CO1-4Cl), achieving a high EQE of 66% at 960 nm (0.5 A W −1 ), a low J d of 7 nA cm −2 at −2 V, and a detectivity around 10 12 Jones.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[7,9] Nonetheless, recent efforts have led to significant boosts in the performance of NIR OPDs using either polymers [10][11][12][13] or small molecule materials. [14][15][16][17][18][19] For instance, Xiong et al investigated solutionprocessed polymer NIR OPDs with PMDPP3T:PC 61 BM bulk heterojunction (BHJ), exhibiting a low dark current density (J d ) of 3.0 nA cm −2 at −0.2 V and a high external quantum efficiency (EQE) of 48% at 850 nm (a responsivity of 0.37 A W −1 ) for broad sensing applications. [11] A further improvement on the device performance has been recently made by introducing a very thick active layer (≈300 nm) with a non-fullerene acceptor (PTB7-Th:CO1-4Cl), achieving a high EQE of 66% at 960 nm (0.5 A W −1 ), a low J d of 7 nA cm −2 at −2 V, and a detectivity around 10 12 Jones.…”
mentioning
confidence: 99%
“…[12] On the other hand, small moleculebased OPDs have also shown promising results, particularly featuring selective response to NIR wavelengths, which are mostly based on porphyrin, [14] squaraine, [15] and phthalocyanine (Pc). [16][17][18][19] Among the molecules, Pc-based NIR photodetectors have recently revealed the outstanding device performance. For example, the OPD with NIR-selective chloroindum Pc in the active layer resulted in a high EQE of 80% at 705 nm, a low J d of 10 nA cm −2 , and a detectivity over 10 12 Jones.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[ 19 ] In addition, we also found that ClAlPc blended with C 70 as an active layer can achieve dark current density <1 nA cm −2 and specific detectivity >4 × 10 13 cm Hz 1/2 W −1 at 730 nm, which might significantly improve the photoresponse property of the organic detectors. [ 21 ] Moreover, ClAlPc shows a high absorption coefficient to cover the UV/NIR region selectively and possess a low highest occupied molecular orbital level to increase the open‐circuit voltage ( V oc ) >0.7 V for OPVs. [ 55 ] In this article, we propose a new approach that uses bulk heterojunction (BH) of ClAlPc:C 60 as the active layer to modify the absorption profile and optical distribution in the device.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, these results not only demonstrate the vacuum‐deposited TPV with the highest AVT's value but also provide a route to fabricate transparent electrode consisting of Cu:Ag metal alloy and capping layer of WO 3 . It is worthwhile to mention that the ultrathin ClAlPc:C 60 active layer shows UV/NIR abosrption ability, which is advanageous for developing a novel light‐sensing or absorption electronics, such as NIR sensitive organic photovoltaics (OPVs), [ 19 ] semi‐TPVs, [ 8 ] multitandem OPVs, [ 20 ] wide‐absorption range organic photodetector, [ 21 ] organic upconversion devices, [ 22 ] etc. On the other hand, to further investigate the optical effect on our proposed TPV, we have used optical modeling to optimize each layer, i.e., organic active layer and transparent electrode for higher transmittance and lower reflection of lights in the devices.…”
Section: Introductionmentioning
confidence: 99%